Persistent, multi-sourced lead contamination in Central Europe since the Bronze Age recorded in the Füramoos peat bog, Germany - Kern, Oliver A.; Koutsodendris, Andreas; Süfke, Finn; Gutjahr, Marcus; Mächtle, Bertil; Pross, Jörg (Anthropocene, 2021)
Despite a multitude of lead-contamination archives, the history of anthropogenic lead (Pb) contamination in Central Europe during the Holocene has remained incompletely understood. Contributing to a regionally differentiated understanding of Pb contamination in Central Europe since the Late Glacial (14.5 kyrs ago), this paper presents a record of atmospheric Pb deposition from an ombrotrophic peat bog at Füramoos, southern Germany. We combine Pb content and isotope data with pollen data allowing the interpretation of Pb signals within a context of natural change and human activities. The data show that Pb accumulation rates during the Late Glacial and early Holocene (0.074 mg*m-2*yr-1) were considerably higher than those during the mid-Holocene (0.016 mg*m-2*yr-1). Anthropogenic Pb contamination commenced at 3600 years BP and originates primarily from the Western Mediterranean region until the demise of the Roman Empire, after which contamination sources shifted to Britain, France, and Germany. For the past 3600 years, the data document an exponential increase in Pb contamination (max 5.6 mg*m-2*yr-1) that is unhinged from natural Pb deposition and far exceeds the natural Holocene background levels. The integrated geochemical and palynological approach allows placement of Pb contamination signals into detailed historical context. Land-use changes at Füramoos are consistent with the timing of political, economic, and social developments of medieval societies that modulated the ability and demand for mining during the past millennia.